An analytic network process model for hospital facilities management performance evaluation. Issue 5 (30th December 2021) - Lai, Joseph H.K.; Hou, Huiying (Cynthia); Edwards, David J.; Yuen, P.L.
Abstract : Purpose: This study aims to establish a rigorous model that can pragmatically evaluate the facilities management (FM) performance of hospitals. Design/methodology/approach: Among the applicable performance indicators that were identified from extant literature, a focus group study shortlisted ten key performance indicators (KPIs) in four categories (safety, physical, financial and environmental) and verified their practicality. Using the analytic network process (ANP) method to process the focus group's responses yielded importance weightings for the KPIs and developed the intended evaluation model. This model was then validated by a case study. Findings: From the empirical data collected, two types of FM performance data and two scenarios of KPI scores were identified. To process these data and scores, a robust calculation method was devised and then proved useful in obtaining an overall score for holistic hospital FM performance. The case study confirmed the appropriateness and validity of the model developed. Research limitations/implications: Through illustrating how the ANP method could be applied to develop an FM performance evaluation model, the study contributes knowledge to the multi-criteria decision-making domain. Despite the geographical limitation of the model established (i.e. centered around a group of hospitals investigated in Hong Kong), the study can serve as a reference for developing performance evaluation models for other buildings or infrastructures globally. Practical implications: The model constitutes a practical tool for evaluating the FM performance of hospitals. Using this model on a regular basis will enable performance benchmarking and hence, continuous improvement of FM services. Originality/value: The ANP model established is the first of its kind tailored for evaluation of hospital FM performance.